The effect of biofeedback intervention program on anxiety among engineering students at Universiti Malaysia Pahang - Prima, Vitasari (2011)
Anxiety is a major predictor of students’ academic performance. High anxiety level has negative effects on their academic performance. Previous research has reported that many university students faced anxieties while undergoing their studies but did not receive adequate intervention program to reduce their study anxiety. Researchers also reported that biofeedback training has been proven to significantly reduce anxiety among individuals. This study was designed to explore anxiety problems faced by university students, and it employs pre post design to compare between groups. It also incorporates biofeedback training in the intervention program in reducing study anxiety for the improvement of students' academic performance. The training group were exposed to ten sessions of training but no intervention was given to the non-training group. Data collection is through a random survey, and the results are used to identify the study anxiety sources among the students. A total 770 engineering students were involved in the survey, while 205 students sat for the correlation test, and 70 students participated in the biofeedback training. The quantitative analysis was used to find significant effect of the intervention program. Study anxiety as an independent variable was measured by physiological arousal and cognitive anxiety. The academic performance uses grade point average (GPA) as a dependent variable. From the survey, seven significant sources of study anxiety were found: examination anxiety (the major source), social anxiety, presentation anxiety, mathematics anxiety, language anxiety, family anxiety, and library anxiety. Using Pearson correlation, a significant correlation between high level anxiety and low academic performance was found, with a small coefficient correlation (r = -.264; p = .000). Results of repeated measure indicated significant differences across 4 sessions in physiological arousal among training group. Using Paired t-test revealed that the training group showed significant reduced on all physiological and cognitive measures while not significant on all measures for non training group. For academic performance, both groups show significant improvement, with p = .000 for the training group and p = .001 for the non-training group. However, as for academic improvement, the training group showed a 25% improvement compared to 7% improvement for the non-training group. Based on the self-evaluation results, the participants in the training group achieved the following positive effects from the training: feel more relaxed and calm, more confident, reduced heartbeat rates, improved breathing techniques, improved study skills, better time management, increased concentration, and improved overall well being. In conclusion, the biofeedback intervention program is definitely effective in helping students reduce their study anxiety in improving academic performance. In addition, the study supported the Catastrophe model to examine the effect of biofeedback intervention program in reducing anxiety for the improvement academic performance.